Synergistic Activation of Human Involucrin Gene Expression by Fra-1 and p300—Evidence for the Presence of a Multiprotein Complex - Crish, James F. (2007)
Involucrin is expressed in the differentiated suprabasal epidermal layers, and an AP1 transcription factor-binding site present in the involucrin promoter distal regulatory region is required for this regulation. This site binds Fra-1, but cofactor interaction at this site has not been adequately characterized. We show that Fra-1 and p300 histone acetyltransferase are present at the AP1 site, as detected by chromatin immunoprecipitation. This interaction is functional, as treating p300 expressing keratinocytes with calcium or 12-O-tetradeconylphorbol-13-acetate, results in a synergistic increase in hINV expression, and this enhanced activation can be reproduced by coexpression of Fra-1 and p300. p300 also co-precipitates with Fra-1, but protein fractionation studies suggest that this interaction requires an additional protein. Fra-1 also interacts with other proteins that interact at the AP1-5 site, including JunD, JunB, Sp1, and P/CAF. Contrary to results in some other systems, Fra-1 functions as a positive transcriptional regulator in human keratinocytes. These studies suggest that a large multiprotein complex, which includes Fra-1, p300, P/CAF, junD, junB, and Sp1 acts at the AP1-5 site to produce a synergistic increase in hINV gene expression.